Upgrading biomass-derived pyrolysis bio-oil to bio-jet fuel through catalytic cracking and hydrodeoxygenation: A review of recent progress. (15th September 2022) - Lahijani, Pooya; Mohammadi, Maedeh; Mohamed, Abdul Rahman; Ismail, Farzad; Lee, Keat Teong; Amini, Ghazaleh
Graphical abstract: Highlights: High oxygen content of biomass-derived bio-oil impedes its use as a drop-in biofuel. Deoxygenation and upgrading of bio-oil via catalytic cracking and hydrodeoxygenation to bio-jet fuel are reviewed. Catalytic cracking generates low-carbon hydrocarbons not meeting jet fuel requirements. Hydrodeoxygenation is a versatile route to produce jet fuel range hydrocarbons from bio-oil. There is a big research gap in hydrodeoxygenation of real bio-oil, not model compounds, to bio-jet fuel. Abstract: Biomass-to-liquid thermochemical routes are the leading green alternatives for producing sustainable hydrocarbon fuels in the near future, including bio-jet fuel. Fast pyrolysis is among the most prospective approaches for converting waste biomass, including agricultural wastes and forestry residues, into liquid fuels. However, despite its maturity, pyrolysis-derived bio-oil bears a poor quality, attributed to the presence of numerous oxygenated compounds and high water content, making it chemically unstable, viscous, and corrosive, with a low heating value. Such inferior properties exclude the direct use of bio-oil as a drop-in fuel, and extensive upgrading is required before it could be utilized as a kerosene fraction and/or blend. Two catalytic post-treatment approaches have shown to be most promising for upgrading bio-oil and refining it to a finished product; catalytic cracking of fast pyrolysis vapor and hydrodeoxygenation. This review focuses on the conversion of biomass-derived bio-oil, excluding triglyceride-based oils, into jet fuel range hydrocarbon through catalytic cracking (associated with catalytic fast pyrolysis) and hydroprocessing (hydrogenation and hydrodeoxygenation), according to the most recent literature efforts. It provides an in-depth overview of the challenges and most recent progress in upgrading real pyrolysis bio-oil to bio-jet fuel through these two routes, emphasizing the conversion pathways. Due to the complex composition of raw bio-oil, very few studies have been devoted to mechanistic aspects of raw bio-oil upgrading, and most studies have been focused on individual model compounds. Hence, research opportunities remain open for extensive studies on real bio-oil upgrading to bio-jet fuels.